Distribution of species of phytophthora affecting coconut and pepper in Kerala - Veena S S (Department of Plant Pathology, College of Agriculture, 1996)
The present investigation was undertaken to correctly identify the species of Phytophthora causing bud rot of coconut and foot rot of pepper in Kerala and to find out their comparative role in causing diseases on coconut and pepper. The study also aimed at isolation of viable antagonistic agents against the pathogen, so as to utilize them in future for biological control. The study was conducted during 1992-96 at College of Agriculture, Vellayani and Indian Institute of Spices Research, Kozhikode. Detailed symptomatology of both the diseases at different locations were studied. Periodic collections were made from diseased coconut and pepper from seven districts of Kerala. The morphological characters of the isolates were studied in detail. The length, breadth, L/B ratio, pedicel length and caducity of sporangia of coconut isolates were smaller than pepper isolates. The sporangial shapes differed considerably between and among the isolates. All the isolates except those collected from Kannur and Kasaragod districts (C7 - C16), produced abundant number of sporangia on carrot agar. Phytophthora are either heterothallic or homothallic. Generally P. palmivora and P. capsici are heterothallic. But ten